Atmospheric Ozone and Methane in a Changing Climate - Ivar Isaksen; Terje Berntsen; Stig Dalsøren; Kostas Eleftheratos; Yvan Orsolini; Bjørg Rognerud; Frode Stordal; Ole Søvde; Christos Zerefos; Chris Holmes (Atmosphere, 2014)
Ozone and methane are chemically active climate-forcing agents affected by climate–chemistry interactions in the atmosphere. Key chemical reactions and processes affecting ozone and methane are presented. It is shown that climate-chemistry interactions have a significant impact on the two compounds. Ozone, which is a secondary compound in the atmosphere, produced and broken down mainly in the troposphere and stratosphre through chemical reactions involving atomic oxygen (O), NOx compounds (NO, NO2), CO, hydrogen radicals (OH, HO2), volatile organic compounds (VOC) and chlorine (Cl, ClO) and bromine (Br, BrO). Ozone is broken down through changes in the atmospheric distribution of the afore mentioned compounds. Methane is a primary compound emitted from different sources (wetlands, rice production, livestock, mining, oil and gas production and landfills).Methane is broken down by the hydroxyl radical (OH). OH is significantly affected by methane emissions, defined by the feedback factor, currently estimated to be in the range 1.3 to 1.5, and increasing with increasing methane emission. Ozone and methane changes are affected by NOx emissions. While ozone in general increase with increases in NOx emission, methane is reduced, due to increases in OH. Several processes where current and future changes have implications for climate-chemistry interactions are identified. It is also shown that climatic changes through dynamic processes could have significant impact on the atmospheric chemical distribution of ozone and methane, as we can see through the impact of Quasi Biennial Oscillation (QBO). Modeling studies indicate that increases in ozone could be more pronounced toward the end of this century. Thawing permafrost could lead to important positive feedbacks in the climate system. Large amounts of organic material are stored in the upper layers of the permafrost in the yedoma deposits in Siberia, where 2 to 5% of the deposits could be organic material. During thawing of permafrost, parts of the organic material that ...